Analisis Konseptual Integrasi Literasi dalam Pembelajaran Tematik pada Kurikulum Merdeka di Sekolah Dasar - Widiono, Andi; Alfarisi, Muhamad; Gunawan, Ade; Prasasti, Adya Rosa; Fikriana, Fikriana Rosa; Sarwendah, Titin Rosa; Putra, Lutfi Guntur Eka (Jurnal Ilmiah Wahana Pendidikan, 2025)
This study aims to analyze the concept of literacy integration in thematic learning within the Independent Curriculum in elementary schools. The method used is a literature study by reviewing various literature sources related to literacy, thematic learning, and the implementation of the Independent Curriculum. The analysis results indicate that literacy integration in thematic learning can improve reading, writing, critical thinking, and conceptual understanding skills holistically. The project-based learning and real-life context offered by the Independent Curriculum support literacy strengthening through reading, discussion, and presentation activities. However, literacy integration is not optimal due to limited teacher competency, minimal reading facilities, and a low student literacy culture. This study recommends strengthening teacher training, providing digital and print-based literacy media, and collaboration between parents and schools in building a culture of literacy from an early age.